Genotyping and Zoonotic Potential of Enterocytozoon bieneusi in Pigs in Xinjiang, China - Li, Dong-Fang; Zhang, Ying; Jiang, Yu-Xi; Xing, Jin-Ming; Tao, Da-Yong; Zhao, Ai-Yun; Cui, Zhao-Hui; Jing, Bo; Qi, Meng; Zhang, Long-Xian (Frontiers in Microbiology, 2019)
Enterocytozoon bieneusi is an obligate intracellular fungus, infecting various invertebrate and vertebrate hosts, it is common in humans and causes diarrhea in the immunocompromised. In the present study, 801 fecal specimens were collected from pigs on seven large-scale pig farms in Xinjiang, China. Nested polymerase chain reaction (PCR) amplification of the internal transcribed spacer (ITS) gene showed that the overall E. bieneusi infection rate was 48.6% (389/801). The E. bieneusi infection rates differed significantly among the collection sites (20.0–73.0%) (χ2 =75.720, df = 6, p < 0.01). Post-weaned pigs had the highest infection rate (77.2%, 217/281), followed by fattening pigs (67.4%, 87/129) and pre-weaned suckling pigs (35.5%, 60/169). Adult pigs had the lowest infection rate (11.3%, 25/222). The E. bieneusi infection rates also differed significantly among age groups (χ2 = 246.015, df = 3, p < 0.01). Fifteen genotypes were identified, including 13 known genotypes (CHC, CS-1, CS-4, CS-7, CS-9, D, EbpA, EbpC, EbpD, H, PigEb4, PigEBITS5, and WildBoar8) and two novel genotypes (XJP-II and XJP-III). Among them, six genotypes (CS-4, D, EbpA, EbpC, H, and PigEBITS5) have been reported in humans. Phylogenetic analysis showed that all the genotypes belonged to Group 1 of E. bieneusi. These findings suggest that pigs may play an important role in transmitting E. bieneusi infections to humans.